Children and media a global perspective - Lemish, Dafna 1951- (West Sussex, UK Wiley-Blackwell, 2015)
"Taking a global and interdisciplinary approach, Children and Media explores the role of modern media, including the internet, television, mobile media and video games, in the development of children, adolescents, and childhood. Primer to global issues and core research into children and the media integrating work from around the world Comprehensive integration of work that bridges disciplines, theoretical and research traditions and methods Covers both critical/qualitative and quantitative approaches to the topic "-- Provided by publisher.
"Children and Media is the definitive overview of the intersection of children and media, which provides a sweeping picture of the field from the accumulated interdisciplinary and global literature of the past 60 years"-- Provided by publisher.
Includes bibliographical references (pages 243-267) and index.
Keywords: Mass media and children